2016
DOI: 10.1017/s2040174416000726
|View full text |Cite|
|
Sign up to set email alerts
|

Childhood body mass index at 5.5 years mediates the effect of prenatal maternal stress on daughters’ age at menarche: Project Ice Storm

Abstract: Early pubertal timing is known to put women at greater risk for adverse physiological and psychological health outcomes. Of the factors that influence girls' pubertal timing, stress experienced during childhood has been found to advance age at menarche (AAM). However, it is not known if stress experienced by mothers during or in the months before conception can be similarly associated with earlier pubertal timing. Prenatal maternal stress (PNMS) is associated with metabolic changes, such as increased childhood… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 96 publications
(153 reference statements)
1
10
0
1
Order By: Relevance
“…An important limitation is the lack of pubertal assessment at 11½ years, the age at which the hormonal collection was done in the context of this study. However, since then, we have collected pubertal staging at ages 13½ and 15½ years, and have found that the majority of girls in our sample (~80%) had their first period after the age of 11½ (mean age of 11.97; Duchesne, Liu, Jones, Laplante, & King, 2017). We ran exploratory analyses using self-reported Tanner staging at 13½ years as our best estimate of pubertal maturation at 11½ (acknowledging the limitations of this approach given the vast individual variability in temporal progression through puberty, but assuming that pubertal status does not regress across time) and did not find any moderation by Tanner stage in either model (data not shown).…”
Section: Discussionmentioning
confidence: 99%
“…An important limitation is the lack of pubertal assessment at 11½ years, the age at which the hormonal collection was done in the context of this study. However, since then, we have collected pubertal staging at ages 13½ and 15½ years, and have found that the majority of girls in our sample (~80%) had their first period after the age of 11½ (mean age of 11.97; Duchesne, Liu, Jones, Laplante, & King, 2017). We ran exploratory analyses using self-reported Tanner staging at 13½ years as our best estimate of pubertal maturation at 11½ (acknowledging the limitations of this approach given the vast individual variability in temporal progression through puberty, but assuming that pubertal status does not regress across time) and did not find any moderation by Tanner stage in either model (data not shown).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, in our previous Project Ice Storm studies, objective hardship was strongly correlated with physical, physiological and cognitive measures (Laplante et al, 2004, 2007, 2008, 2016; King and Laplante, 2005; King et al, 2009, 2012). Also, it was reported that objective hardship was strongly associated with DNA methylation (Cao-Lei et al, 2015, 2016), insulin secretion (Dancause et al, 2013), cytokine production (Veru et al, 2015), and earlier age at menarche (Duchesne et al, 2017), suggesting that the mechanisms through which objective hardship affects offspring development may bypass the maternal HPA axis and use other pathways to influence development of these systems. Lastly, our present findings linking subjective and/or objective PNMS with externalizing problems are supported by previous Project Ice Storm findings with assessments done 4½, 5½, 6½, 8½, and 9½ and 11½ years of age (King et al, 2012; Nguyen et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have evaluated effects of natural disasters or world pandemics on offspring development [26,27]. Project Ice Storm, which refers to a series of prospective studies on women who were pregnant during one of Canada's worst natural disasters in history, the January 1998 Quebec ice storm, was designed to study the effects of in utero exposure to varying levels of prenatal maternal stress (PNMS), resulting from an independent stressor on the children's development from birth through childhood [28][29][30][31]. Jones et al showed that higher levels of objective PNMS were associated with more externalizing problems (e.g., aggressive behavior), which was in part mediated by measurable differences in amygdala development in the offspring.…”
Section: Discussionmentioning
confidence: 99%